Ankle taping does not impair performance in jump or balance tests - Abián-Vicén, Javier; Alegre, Luis M; Fernández-Rodríguez, J Manuel; Lara, Amador J; Meana, Marta; Aguado, Xavier (Journal of sports science & medicine, 2008)
This study aimed to investigate the influence of prophylactic ankle taping on two balance tests (static and dynamic balance) and one jump test, in the push off and the landing phase. Fifteen active young subjects (age: 21.0 ± 4.4 years) without previous ankle injuries volunteered for the study. Each participant performed three tests in two different situations: with taping and without taping. The tests were a counter movement jump, static balance, and a dynamic posturography test. The tests and conditions were randomly performed. The path of the center of pressures was measured in the balance tests, and the vertical ground reaction forces were recorded during the push-off and landing phases of the counter movement jump. Ankle taping had no influence on balance performance or in the push off phase of the jump. However, the second peak vertical force value during the landing phase of the jump was 12% greater with ankle taping (0.66 BW, 95% CI -0.64 to 1.96). The use of prophylactic ankle taping had no influence on the balance or jump performance of healthy young subjects. In contrast, the taped ankle increased the second peak vertical force value, which could be related to a greater risk of injury produced by the accumulation of repeated impacts in sports where jumps are frequently performed. Key pointsAnkle taping has no influence on balance performance.Ankle taping does not impair performance during the push-off phase of the jump.Ankle taping could increase the risk of injury during landings by increasing peak forces.